THE EFFECT OF EXERCISES WITH INTERACTIVE TOOLS IN LEARNING PASSING AND SCORING SKILLS OF FUTSAL FOR STUDENTS - Bsc. Raad Ali Hussein, Prof. Dr. Haitham Mohammed Kadhim, Assist. Prof. Dr. Taher Yahya Ibrahim (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The futsal game is distinguished by its peculiarity because it possesses the elements of excitement and suspense, the principle adopted by researchers in developing the learning process through exercises with interactive tools that are in the form of stations independent from each other in which skill exercises are given that develop the skills of passing and scoring in the game of futsal and these tools have a clear effect in The learning process raises the two sides of suspense, excitement, gaining time, and performing the skillful duty interactively, and after applying exercises to the research sample, the results of the research came in an encouraging way in favor of the experimental group and the level of performance developed in a clear manner compared to the control group. The researchers recommended the necessity of adopting interactive tools in learning for its great role in increasing suspense, excitement and simulation.